THE IMPLEMENTATION OF 8 TEACHING SKILLS IN MICROTEACHING COMPETENCE TEST IN ENGLISH EDUCATION PROGRAM AT UNIVERSITAS MUHAMMADIYAH BENGKULU - Rianti, Restu; Ivan Achmad Nurcholis; Ria Anggraini; WasluRachim Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
the purpose of this research was to find out how the students implemented the 8 teaching skills in Microteaching competence test. The method used in this research used qualitative research because it refers to research about persons’ lives, behaviour, and stories, but also organizational functioning, social movement or interactional relationships. The researcher used a descriptive qualitative method by compiling or classifying, analyzing, and interpreting the data and using observation as the instrument of the research the subjects of this research are sixth-semester English Education students of Universitas Muhammadiyah Bengkulu who joined the Microteaching course in 2024. the information was gathered directly from people who had experienced the course of Microteaching. The result the student's 8 teaching skills overall marks result are 9.28% bad, 52.4% good, and 38.3% very good. With the individual and grouping skill at 11.7% of students mark with “bad”, and with discussion skill at 64.3% marked “good” and 21.1% marked “very good”. And suggested students need to improve strategies, self-reflect on what they should improve, Try to include all teaching skills when performing microteaching.